A “Her-Storical” Conceptualization of the “Umuada” Traditional Institution of Eastern Nigeria - Ayeni, Queen Olubukola; Ben, Anthony Okon (The Gender Truth Journal, 2025)
This study explores a sociocultural organization of women in Eastern Nigeria through the lens of feminist and historical scholarship. The aim is to examine the historical evolution, roles, and contributions of the Umuada within their communities, particularly in conflict resolution, cultural preservation, and socioeconomic development. Utilizing a qualitative methodology, the research draws from oral histories, archival records, and ethnographic observations to provide a nuanced understanding of the institution. The findings reveal that the Umuada, far from being a peripheral group, have played pivotal roles as custodians of traditions, mediators in family and communal disputes, and advocates for women’s rights within the patriarchal structure of Igbo society. Despite these contributions, the study highlights the challenges posed by modernity, urbanization, and diminishing communal ties to the relevance and functionality of the institution. Major conclusions emphasize the need to reimagine and integrate the Umuada into contemporary frameworks for community development and gender advocacy, by ensuring their sustained impact in a rapidly changing sociocultural landscape. By foregrounding the experiences and agency of these women, the study contributes to the broader discourse on African feminism and indigenous knowledge systems.